Comparison of selected tools for automation testing of Web applications - Piotr Pasławski; Maciej Pańczyk (Journal of Computer Sciences Institute)
The article is as an introduction to software testing, considering its definition and reasons for errors appearing in code. Three selected libraries available in Python, used for automating tests of web applications, are presented: Selenium, Playwright, and Splinter. Subsequently, a detailed comparison of these tools is made based on specific comparative criteria.